-5=-y+2

Simple and best practice solution for -5=-y+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=-y+2 equation:


Simplifying
-5 = -1y + 2

Reorder the terms:
-5 = 2 + -1y

Solving
-5 = 2 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-5 + y = 2 + -1y + y

Combine like terms: -1y + y = 0
-5 + y = 2 + 0
-5 + y = 2

Add '5' to each side of the equation.
-5 + 5 + y = 2 + 5

Combine like terms: -5 + 5 = 0
0 + y = 2 + 5
y = 2 + 5

Combine like terms: 2 + 5 = 7
y = 7

Simplifying
y = 7

See similar equations:

| 4x-5y=-8 | | -b=-8+b | | 5x-7=-127 | | X=-0+2 | | (3)=-7x | | 3=-7x | | -7+k/5=-5 | | 1+5b=-19 | | 16-0.7(R-5)=(7R-5) | | x/2-1=3 | | x^2+12x+36=144 | | 4a+ab= | | -10-f=10+3f | | (X^4-1)(X^2+11)=0 | | y/6-5/8=2 | | -20=-4x-12 | | -1=-8+b/6 | | 3+5lnx=9 | | 3(4x+5x)=204 | | 0.18(24)+0.02X=0.06(24+X) | | -5-2y=-1 | | a-4=2x+1-5x | | 8+11P-4=6P+18-2P | | s-19=-3 | | X-2(-5)=-1 | | Log(x+10)-log(2)=log(3x+2) | | 2(3x-4)+7(4-x)=4x | | X-2(1)=-1 | | 4x+8=8-2x | | 7-4(3x-2)=9 | | -6-7m=72 | | 3x^3+12x^2+16x+8=0 |

Equations solver categories